2002
DOI: 10.1177/019394502320555430
|View full text |Cite
|
Sign up to set email alerts
|

Animal-Assisted Therapy and Nutrition in Alzheimer’s Disease

Abstract: This study examined the influence of animal-assisted therapy, specifically fish aquariums, on nutritional intake in individuals with Alzheimer's disease (AD). Sixty-two individuals with AD who lived in specialized units were studied. Baseline nutritional data were obtained followed by a 2-week treatment period when the aquariums were introduced. The treatment data were collected daily for 2 weeks then weekly for 6 weeks. Nutritional intake increased significantly (21.1%; p <.001) when the aquariums were introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
145
0
27

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(177 citation statements)
references
References 28 publications
2
145
0
27
Order By: Relevance
“…Following extensive literature review, we found no study to date that investigated the use of AAT for persons with stroke or aphasia. Despite the lack of research in AAT for persons with aphasia, numerous studies have been performed on the effects of AAT on other adult populations, such as residents of nursing homes [9][10][11][12]; patients in acute-care hospitals [13][14][15][16]; patients in intensive care units [17]; and adults with spinal cord injury [18], dementia [19][20], depression [21], psychiatric disorders [21][22][23], and schizophrenia [24][25][26].…”
Section: Animal-assisted Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Following extensive literature review, we found no study to date that investigated the use of AAT for persons with stroke or aphasia. Despite the lack of research in AAT for persons with aphasia, numerous studies have been performed on the effects of AAT on other adult populations, such as residents of nursing homes [9][10][11][12]; patients in acute-care hospitals [13][14][15][16]; patients in intensive care units [17]; and adults with spinal cord injury [18], dementia [19][20], depression [21], psychiatric disorders [21][22][23], and schizophrenia [24][25][26].…”
Section: Animal-assisted Therapymentioning
confidence: 99%
“…Edwards and Beck took a more unique approach and studied whether the presence of fish aquariums influenced the nutritional intake of individuals with Alzheimer's disease (AD) [20]. They studied 62 individuals with AD who lived in specialized units.…”
Section: Animal-assisted Therapymentioning
confidence: 99%
“…It has been shown that aquarium keeping improves human well-being in many aspects, e.g. the development of responsibility in children (Edwards, Beck, 2002), reduction of stress levels in adults, and improved physical and psychological well-being in the elderly (Reaser, Meyers, 2007). The United States is the leading country in the number of hobbyists, with about 20 million enthusiasts (Chapman, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…When fish tanks were introduced into a nursing home environment to test the effects on residents, observers found an overall increase in nutrition on the part of the participating residents [30]. A sideeffect of the installation of the fish tanks was that residents gathered around those situated in common areas and engaged in more conversation than was previously observed.…”
Section: Assistive Evaluationmentioning
confidence: 91%
“…Paro [134,135], an actuated stuffed seal, behaves in response to touch and sound. Its goal is to provide the benefits of pet-assisted therapy, which can affect resident quality of life [30], in nursing homes that cannot support pets. Initial studies have shown lowered stress levels in residents interacting with this robot, as well as an overall increase in the amount of socialization among residents in the common areas of the same facility.…”
Section: Social Service and Assistive Roboticsmentioning
confidence: 99%